Genetic Techniques Used in the Diagnosis of Inherited Platelet Disorders - Mumford, Andrew D.; Westbury, Sarah K. (Seminars in Thrombosis and Hemostasis, 2019)
Recent advances in genetic analysis are bringing huge benefits to patients with rare genetic disorders, including those with inherited disorders of platelet number and function. Modern clinical hematological practice now has a range of genetic techniques available to enable the precision diagnosis of inherited platelet disorders (IPDs). There are some features of this disparate group of inherited disorders that present specific challenges to establishing an accurate genetic diagnosis. This review aims to introduce the techniques that are relevant for the genetic diagnosis of IPDs and will discuss the key considerations necessary for their application to the clinic.
Keywords: platelets; genetics; diagnosis; high-throughput sequencing